2022
DOI: 10.2147/ijgm.s353708
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Hub Genes with Poor Prognosis in Hepatocellular Carcinoma by Integrated Bioinformatical Analysis

Abstract: Background: Hepatocellular carcinoma (HCC) is the reason for the world's second largest cancer-related death. It is clinically valuable to study the molecular mechanisms of HCC occurrence and development for formulating more effective diagnosis and treatment strategies. Methods: The five microarray data sets GSE45267, GSE101685, GSE84402, GSE62232 and GSE45267 were downloaded from Gene Expression Omnibus (GEO) database, including 165 HCC tissues and 73 normal tissues. Differential expressed genes (DEGs) betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Related studies have also shown high levels of AURKA as an indicator of poor prognosis in bladder cancer. It is also associated with the development and prognosis of rectal cancer, hepatocellular carcinoma, and head and neck cancer ( Lu et al, 2021 ; Tsepenko et al, 2021 ; Guo et al, 2022 ; Huang et al, 2022 ). This research discovered that high AURKA was related to a bad prognosis in various malignancies by creating a deep forest graph and feeding back the association between AURKA, overall survival, and disease-specific survival.…”
Section: Discussionmentioning
confidence: 99%
“…Related studies have also shown high levels of AURKA as an indicator of poor prognosis in bladder cancer. It is also associated with the development and prognosis of rectal cancer, hepatocellular carcinoma, and head and neck cancer ( Lu et al, 2021 ; Tsepenko et al, 2021 ; Guo et al, 2022 ; Huang et al, 2022 ). This research discovered that high AURKA was related to a bad prognosis in various malignancies by creating a deep forest graph and feeding back the association between AURKA, overall survival, and disease-specific survival.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have investigated AURKA expression across publicly available gene expression datasets, all highlighting the higher expression of AURKA in tumours compared to non-cancerous tissues (Table 1). [66][67][68][69][70][71][72][73][74][75][76][77][78] AURKA showed a marked increase in Hepatitis B virus + (HBV + ) HCC samples compared to the paired HBV + non-tumoural liver tissues in GSE14520 [128.00 (78.79-219.79) 68 By using integrated bioinformatics analyses, most of these studies have identified AURKA as one of the central hub genes with crucial functions in HCC. [68][69][70][71][72][73][75][76][77] Other studies have independently supported this evidence, such as the research conducted by Jeng and colleagues.…”
Section: Expression Pattern Of Aurka In Hccmentioning
confidence: 99%
“…[66][67][68][69][70][71][72][73][74][75][76][77][78] AURKA showed a marked increase in Hepatitis B virus + (HBV + ) HCC samples compared to the paired HBV + non-tumoural liver tissues in GSE14520 [128.00 (78.79-219.79) 68 By using integrated bioinformatics analyses, most of these studies have identified AURKA as one of the central hub genes with crucial functions in HCC. [68][69][70][71][72][73][75][76][77] Other studies have independently supported this evidence, such as the research conducted by Jeng and colleagues. They observed AURKA overexpression in tumours compared to the distal portion of the liver collected from 137 HCC patients at the local hospital (Table 2).…”
Section: Expression Pattern Of Aurka In Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…nlm.nih.gov/geo/ and https://portal.gdc.cancer.gov/. The "limma" package was applied to perform deduplication and log2(x + 1) normalization processing on gene expression data (8).…”
Section: Data Obtaining and Processingmentioning
confidence: 99%